2009
DOI: 10.1089/end.2009.1534
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy for Staghorn Calculi: A Single Center's Experience over 15 Years

Abstract: PCNL is a safe and effective procedure in the management of staghorn calculi, with outcomes similar to those reported for percutaneous management of smaller volume nonstaghorn stones. Attention to accurate tract selection and placement as well as possession of the full array of endourologic equipment are essential to achieving an excellent outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
7
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 15 publications
5
49
7
1
Order By: Relevance
“…They included subject criteria similar to our study, namely the complete and partial staghorn calculi 14 . However, the stone-free rate of our study was lower than that reported by Soucy et al 13 who reported higher stone-free rate (78%). That study incorporated branched stone in just one calyx (borderline staghorn calculi) found in 67% of their patients, so that the majority of patients had a lower burden stone and were easier to treat 13 .…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…They included subject criteria similar to our study, namely the complete and partial staghorn calculi 14 . However, the stone-free rate of our study was lower than that reported by Soucy et al 13 who reported higher stone-free rate (78%). That study incorporated branched stone in just one calyx (borderline staghorn calculi) found in 67% of their patients, so that the majority of patients had a lower burden stone and were easier to treat 13 .…”
Section: Discussioncontrasting
confidence: 89%
“…The goal treatment of staghorn calculi is stone-free thoroughly with minimal morbidity 1, 11 . PCNL in patients with staghorn calculi still represents a procedural challenge, thus requiring the surgeon to perform complete removal of the stone while keeping morbidity to a minimum 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the stone clearance rate, Falahatkar et al in their series, they achieved 87.5% stone clearance rate, Soucy et al report 91% stone clearance rate at three months follow up for partial or complete staghorn stones using single or multiple tracts. 25 Our study revealed 97% stone clearance rate and 3% with clinically insignificant fragments following PCNL monotherapy compares favorably with the results ofothers. [26][27][28] PCNL is a safe and effective method of stone removal in patients with calculi in horseshoe kidneys.…”
Section: Discussionsupporting
confidence: 82%
“…Staghorn calculi may not always be investigated for underlying cystinuria, because it may be falsely assumed that they are infective stones, struvite in origin, and composed of magnesium ammonium phosphate. Case series reported by Soucy et al (26) and Viprakasit et al (27) have shown that between 21% and 44% of staghorn calculi are struvite, and for the remainder, other etiogic causes should be sought. Cystinuria is a known and important cause of staghorn calculi.…”
Section: Discussionmentioning
confidence: 99%